Comprehensive agrobiological assessment and analysis of genetic relationships of promising walnut varieties of the Nikitsky Botanical Gardens - Yu. V. Plugatar; I. I. Suprun; S. Yu. Khokhlov; I. V. Stepanov; E. A. Al-Nakib (Вавиловский журнал генетики и селекции)
Walnut is an important horticultural crop, the production of which ranks second among all nut crops. Despite the significant demand in the domestic market in Russia, the industrial production of walnut fruits in Russia is currently underdeveloped. At the same time, there is a need to update the assortment with new highly productive varieties adapted to local agro-climatic conditions and having high quality nuts that are competitive at the world level. An important issue for the successful implementation of breeding programs is a comprehensive study of the gene pool. In this regard, within the framework of the study, the task was to evaluate promising varieties from the collection of the walnut gene pool of the Nikitsky Botanical Gardens and analyze genetic relationships based on microsatellite genotyping. On the basis of the performed phenotypic assessment, the study sample, which included 31 varieties, was divided into several groups according to the main phenotypic traits, such as frost and drought resistance, the start of the growing season, the ripening period, the weight and type of flowering, the weight of the fruit, and the thickness of the endocarp. Varieties with economically valuable traits that can be recommended as promising as initial parental forms in breeding work for resistance to abiotic stress factors have been identified, as well as varieties with increased productivity and large fruit sizes. Based on the analysis of eight SSR markers (WGA001, WGA376, WGA069, WGA276, WGA009, WGA202, WGA089 and WGA054), an analysis of the level of genetic diversity was performed and genetic relationships were established in the studied sample of varieties. Six (for WGA089) to eleven (for WGA276) alleles per locus have been identified. A total of 70 alleles were identified for the eight DNA markers used, with an average value of 8.75. Analysis of SSR genotyping data using Bayesian analysis established the presence of two main groups of genotypes. Taking into account the fact that all the studied varieties are selections from local seed populations in different regions of the Crimean Peninsula, the revealed level of polymorphism may indirectly reflect the level of genetic diversity of the local walnut populations. Furthermore, the presence of two genetically distant groups indicates the presence of two independently formed pools of the autochthonous gene pool of the species Juglans regia L. on the Crimean Peninsula